Effect of The Dolmix KR Drink Preparation on The Physiological Parameters of Rabbits - Dusmurat, Eshimov; Muratbay Uli, Tolibaev Ibrayim (American Journal of Biomedicine and Pharmacy, 2026)
This article presents the results of experimental studies on the effect of the Dolmix KR Drink preparation on certain morphological parameters of rabbit blood. Administration of Dolmix KR Drink to rabbits at two months of age ensures the maintenance of blood parameters within physiological norms. When the preparation was administered at a dose of 10 mg/kg of feed, the number of erythrocytes increased by 3.4%, 6.0%, and 7.2% on the 10th, 20th, and 30th days of the experiment, respectively, while hemoglobin levels increased by 4.1%, 7.0%, and 7.9%. In the third experimental group, rabbits receiving 15 mg/kg of feed for 30 days showed increases in erythrocyte counts of 7.0%, 10.2%, and 7.3% on the 10th, 20th, and 30th days, respectively. In the fourth group, the number of erythrocytes per 1 mm³ of blood increased by 9.6%, 12.0%, and 11.8% compared to the control group.